Impact of climatic extremes on Alpine ecosystems during MIS 3. (1st July 2020) - Stojakowits, Philipp; Mayr, Christoph; Lücke, Andreas; Wissel, Holger; Hedenäs, Lars; Lempe, Bernhard; Friedmann, Arne; Diersche, Volker
Abstract: The effects of climatic extremes on Alpine ecosystems, such as in the last glacial period, are poorly understood. The recently discovered Nesseltalgraben site is currently the best dated and most complete high-resolution sedimentary sequence in the northern Alps covering the Marine Isotope Stage (MIS) 3 around 59-28 calibrated kiloyears before present (ka cal BP). The MIS 3 is a period with frequent climatic fluctuations known as Dansgaard-Oeschger cycles or Greenland interstadials-stadials. Here, we present pollen assemblages, bryophyte macrofossils, and stable isotopes (δ 2 H, δ 13 C, δ 18 O) from the Nesseltalgraben to elucidate palaeoenvironments and palaeoclimatic variability during that period. In addition to bulk sedimentary cellulose, also cellulose extracted from fossil wood, monocots, and bryophytes was analysed isotopically. Among the terrestrial pollen, Poaceae and arboreal pollen show an antithetic behaviour reflecting interstadial-stadial variations. Arboreal pollen are dominated by Pinus sylvestris -type, with admixtures of Picea, Betula, Alnus, and Salix . The arboreal pollen record exhibits several maxima indicating milder climatic conditions tentatively assigned to Greenland interstadials 17–14, 12/11, 8, and 6. During Heinrich events 5 and 4, the arboreal pollen record shows distinct minima underlining a severe impact of these events on regional climate and vegetation. Bryophyte assemblages show predominant wetland conditions at the site during the entire MIS 3. The sudden occurrence of the bryophyte Drepanocladus turgescens after 31.6 ka cal BP indicates a change from a fen to a frequently drying wetland environment. This habitat change is presumably linked to enhanced glaciofluvial action caused by glaciers approaching the site. Carbon, hydrogen, and oxygen stable isotope records of bulk sedimentary cellulose exhibit comparably stable conditions from 59 until 52 ka cal BP and increased values around 51 ka cal BP followed by a period of almost absent cellulose until 39 ka cal BP. Thereafter, and lasting until 30 ka cal BP, bulk sedimentary cellulose isotope records (δ 2 H, δ 13 C, and δ 18 O) reveal strongly fluctuating values. These isotope variations are interpreted as variable mixtures between terrestrial lignified plants and monocots on the one, and wetland bryophyte sources on the other hand. A strong negative isotope excursion in the bulk sedimentary and the bryophyte cellulose records around 36.4 ka cal BP is contemporaneous with maximum Cyperaceae pollen and best explained by progressively waterlogged soils due to permafrost. The rise in the bryophyte δ 18 O record thereafter, accompanied by likewise increasing δ 13 C values, most likely indicates an enhanced evaporation of source waters. Highlights: Alpine palaeoenvironments are inferred from a sediment record of MIS 3 age. Arboreal pollen fluctuations reflect stadial-interstadial climate variations. Bryophyte assemblages indicate predominance of wetland habitats. Stable isotopes of bulk cellulose were controlled by local vegetation changes. Source water isotope variability is reconstructed from bryophyte isotope values.